Knowledge automation : how to implement decision management in business processes - Fish, Alan N. (Wiley Corporate F&A., 2012)
A proven decision management methodology for increased profits and lowered risksKnowledge Automation: How to Implement Decision Management in Business Processes describes a simple but comprehensive methodology for decision management projects, which use business rules and predictive analytics to optimize and automate small, high-volume business decisions. It includes Decision Requirements Analysis (DRA), a new method for taking the crucial first step in any IT project to implement decision management: defining a set of business decisions and identifying all the information--business knowledge a.